A case of catastrophic epistaxis from the internal carotid artery due to multiple surgeries and irradiations for pituitary tumor: Rescued utilizing high‐flow bypass and simultaneous skull base reconstruction. Issue 8 (25th August 2021) - Takabayashi, Kosuke; Takebayashi, Seiji; Sakurai, Juro; Gotoh, Shuho; Takizawa, Katsumi
Abstract: Revascularization for internal carotid artery rupture should be considered immediately under the situation where endovascular treatment is not indicated. Revascularization can prevent the risk of hemorrhage during skull base reconstruction. Abstract : Revascularization for internal carotid artery rupture should be considered immediately under the situation where endovascular treatment is not indicated. Revascularization can prevent the risk of hemorrhage during skull base reconstruction.